Enhancing the quality of tourism communication: the effectiveness of inquiry strategies in intercultural contexts - Abdul Rashid, Roswati; Mansor, Noor Rohana; I., Radhiah; C. A., Nurul Ain; Z., Rosdi; Mamat, Roslina (Science Publishing Corporation, 2018)
Inquiry is one of the activities that take place during conversation throughout our daily lives. It has been said that the knowledge that is obtained by an individual start by asking questions. Furthermore, inquiry is identified as an effective communication strategy which is able to influence learning and which is also able to deliver the content of learning. This leads to an increased level of achievement by a learner. However, in reality, a strategy of inquiry does not only focus on the context of communication learning but it also plays an important role in other domains of social communication. Thus, this paper discusses the aspect of mindfulness which outlines the strategy of inquiry to increase the effectiveness of communication between a tour guide and the targeted tourists in the tourism industry during tour visits. The mindfulness aspect of this research is based on the Cross-Cultural Mindfulness Model. It is important to emphasise the mindfulness aspect of inquiry strategies, so that any cross cultural communication will not create conflicts or cultural contradictions. Furthermore, it can assist in smoothing a tour session while increasing the quality of communication in tourism.